1988
DOI: 10.1002/mus.880110418
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular disorders and thymoma

Abstract: We describe a patient who had asymmetrical atrophy of limb muscles and myasthenic weakness of neck, facial, and bulbar muscles. Electrophysiological tests indicated myasthenia gravis of facial muscles and changes consistent with an asymmetrical motor neuropathy as a cause of the muscle atrophy. Both conditions occurred as complications of a locally invasive thymoma, and both failed to improve after surgery and radiation but substantially improved with subsequent treatment by corticosteroids, azathioprine, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Focal atrophy, shown electrophysiologically and morphologically to be due to denervation, may occur in the limbs of at least 10% of patients who have myasthenia gravis. 1,6,16,23 Since morphological studies have shown that the nerve is not directly affected, it has been concluded that this is a ''functional denervation'' due to the reduction in the trophic effects of acetylcholine release on the muscle fiber membrane. 16 A similar mechanism was likely operative in the diaphragm of our patients.…”
Section: Discussionmentioning
confidence: 98%
“…Focal atrophy, shown electrophysiologically and morphologically to be due to denervation, may occur in the limbs of at least 10% of patients who have myasthenia gravis. 1,6,16,23 Since morphological studies have shown that the nerve is not directly affected, it has been concluded that this is a ''functional denervation'' due to the reduction in the trophic effects of acetylcholine release on the muscle fiber membrane. 16 A similar mechanism was likely operative in the diaphragm of our patients.…”
Section: Discussionmentioning
confidence: 98%
“…Heidenreich et al [5] fand bei einem Patienten mit Thymom und Isaacs-Syndrom Antikörper gegen spannungsabhän-gige neuronale K + -Kanäle, der von Witt et al beschriebene Patient [14] hatte wie unser Patient erhöhte GM-1-Antikörper. Watanabe [13] berichtet über einen Patienten mit Thymom und PNP, der wie der von uns betreute eine ausgeprägte vegetative Symptomatik mit Kreislaufkrisen und SIADH aufwies.Ein kurz vor dem Tod unseres Patienten aufgetretener Vorderwand-Herzinfarkt verlief aufgrund dieser vegetativen Mitbeteiligung stumm und fiel nur durch Dyspnoe auf.…”
Section: Zusammenfassung Und Diskussionunclassified